Characters in Fire Emblem Three Houses: A Ludo Mix Perspective - Blom, Joleen (Transactions of the Digital Games Research Association, 2021)
The article focuses on how dynamic game characters create friction in a ludo mix strategy consisting of primarily ludic media, disturbing the narrative coherency that trans- or cross-media strategies strive for. In particular, dynamic game characters, with a development structure that the player influences, cause narrative inconsistencies with the character’s transmedia appearances. Yet, in Japanese media and ludo mixes, character proliferation is the norm so that different versions of the same character can exist without any issues of narrative coherency. Through a case study of the Fire Emblem: Three Houses ludo mix, this article argues that the Japanese concept of the kyara, a proto-character, demonstrates to be an excellent means to avoid a clash between the dynamic game character in one work and its appearance in another work. It concludes that through the use of the kyara, the IP owner avoids any clash between the dynamic game character’s appearance in its source work and its appearance in other ludic works, thereby giving the impression that the player’s agency over the dynamic game character stays intact.